Programmed Band Gap Modulation within van der Waals Semiconductor Monolayers by Metalorganic Vapor-Phase Epitaxy - Lee, Chang-Soo; Jin, Gangtae; Seo, Seung-Young; Kim, Juho; Han, Cheolhee; Park, Min Yeong; Ahn, Heonsu; Lee, Suk-Ho; Cha, Soonyoung; Jo, Moon-Ho (Chemistry of materials, 2020)
Programmed alloying within a van der Waals (vdW) semiconductor monolayer (ML) is achieved by metalorganic vapor-phase epitaxy. Specifically, two versions of on-ML alloying are demonstrated by precise controls of time-lapse vapor pressures during the single-crystalline WS2x Se2(1–x) ML growth, where the alloying degree, x, is either continuously or discretely directed on the MLs in the entire range of 0 ≤ x ≤ 1. With this, on-ML band gap modulation is accomplished in the forms of either graded or discrete intra-ML junctions, leading to atomically thin multispectral photodetectors by a spatially resolved manner at the nanoscales.